Self-healing thermally conductive adhesives. (January 2014) - Lafont, Ugo; Moreno-Belle, Christian; van Zeijl, Henk; van der Zwaag, Sybrand
Thermally conductive composites with a temperature-triggered self-healing response were produced by dispersing boron nitride or graphite particles into two types of polysulphide-based thermoset matrices. The composites produced exhibit recovery of both cohesion and adhesion properties upon thermally activated healing. Using a mild healing temperature (65°C), the materials show full recovery of their initial adhesive strength during multiple healing cycles. The composites behave differently regarding the cohesion recovery: 20%–100% recovery is achieved depending on the filler type, filler loading and the type of matrix. The thermal conductivity of the composites increases with the amount of filler. Values of 1 and 2 W/m K can be achieved for the boron nitride and graphite-based composite, respectively. The results presented in this work clearly show that multifunctional materials with different functionalities and mechanical self-healing responses can be designed using this strategy.